2007
DOI: 10.1515/revneuro.2007.18.6.473
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dopaminergic Synapse In Vivo. II. Molecular Imaging Studies in Small Laboratory Animals

Abstract: Dopaminergic synaptic function may be assessed either at the presynaptic terminal or at the postsynaptic binding sites using molecular in vivo imaging methods. Apart from the density of binding sites, parameters such as alterations in dopamine synthesis, dopamine storage or dopamine release can be quantified either by application of specific radiotracers or by assessing the competition between the exogenous radioligand and endogenous dopamine. The performance of animal studies allows the induction of specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…During the last decades, small animal imaging has been increasingly employed to study neurochemical and physiological parameters such as perfusion, glucose utilization, or receptor and transporter binding in suitable animal models of human disorders (for review, see Nikolaus et al, 2004Nikolaus et al, , 2007b. As, for ethical reasons, numerous scientific questions cannot be assessed in humans, a complementary approach in SZ research can be the performance of investigations on certain presynaptic and/or postsynaptic constituents in suitable animal models such as neonatal ventral hippocampal lesion rat (NVHL; for review, see Lipska and Weinberger, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, small animal imaging has been increasingly employed to study neurochemical and physiological parameters such as perfusion, glucose utilization, or receptor and transporter binding in suitable animal models of human disorders (for review, see Nikolaus et al, 2004Nikolaus et al, , 2007b. As, for ethical reasons, numerous scientific questions cannot be assessed in humans, a complementary approach in SZ research can be the performance of investigations on certain presynaptic and/or postsynaptic constituents in suitable animal models such as neonatal ventral hippocampal lesion rat (NVHL; for review, see Lipska and Weinberger, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a brain imaging study of subjects with depression (Argyelan et al, 2005) demonstrated that chronic bupropion HCl treatment is associated with diminished dopamine transporter availability, which would presumably increase intrasynaptic DA since the dopamine transporter is primarily responsible for clearance of intrasynaptic DA (Hoffman et al, 1998). These studies suggest that chronic bupropion HCl treatment leads to increased intrasynaptic DA, which would be expected to result in a downregulation of D2 receptors and diminished DA release in response to pharmacological stimuli (Bilder et al, 2004; Nikolaus et al, 2007a; Nikolaus et al, 2007b; Bamford et al, 2008). As for evidence of unchanged smoking-induced DA release, a recent study of rodents demonstrated that chronic bupropion HCl treatment increases extracellular DA in the nucleus accumbens shell, but does not alter the reward-facilitating effects of experimenter-administered nicotine (Paterson et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Fortunately, the tools available to link DAT biology to its function in the nervous system are quite extensive and powerful. In particular, imaging modalities for DAT using single positron emission computed tomography (SPECT) and PET with a host of available ligands will provide a crucial link among clinical characterizations, genetic investigations, and basic science studies (19,20). For DAT, effects of alterations in protein structure on the response to pharmacological agents are also providing insights.…”
Section: Transport To the Futurementioning
confidence: 99%